To the question of the formation of syntactic skills in elementary school students in multicultural classes - Mastiaeva E. V. (Current trends in the development of education system, 2020)
The article discusses the basic skills that can be used to judge the level of syntax of the Russian language in primary school students. The main differences in the construction of sentences in the Russian and Tajik languages ​​are presented. And also indicated some difficulties in mastering the syntax of a child-inofon.
Keywords: русский язык; предложение; Russian language; синтаксические умения; инофон; таджикский язык; Syntactic skills; inofon; Tajik language; sentences